Twitter and Tear Gas: The Power and Fragility of Networked Protest - Alsadawi, Ayman (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
Review of: Twitter and Tear Gas: The Power and Fragility of Networked Protest by Zeynep Tufekci. Yale University Press, 2017. 360 pp. $26 (hardcover). $16 (paper).